Construction and standardization of tools for measuring the tendency to modernity in students - Pashm Foroush, Maryam; Karami, Abolfazl; Moradi, Shahab; Sedaghat, Mastooreh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: The issue of transition from traditional society to modern society has been one of the main topics of sociology since the end of World War I. The aim of this study was to construct and standardize the modernity tendency questionnaire by analyzing the factors and measuring its validity and reliability. Methods: The present study was exploratory. The statistical population of this study was all students studying in the academic year of 2008-2009 in Payame Noor Universities in Tehran province. For this purpose, 895 students of Payame Noor University of Tehran completed the designed tool in the academic year of 2008-19. For this purpose, first, the theoretical foundations of previous researches were studied and then a questionnaire was designed based on the areas of the mentioned structure obtained from the study of the resources. After examining the face and content validity of the questions made in relation to each subtest and removing inappropriate questions from it, a total of 58 questions were selected for final implementation on the sample by multistage cluster random sampling. Principal component analysis and varimax rotation method and its reliability with Cronbach's alpha coefficient and retesting were investigated. Results: The results showed that the sampling quality index (KMO) was 0.828 and the significance level of Bartlett's spherical test was less than 0.001. Five factors were extracted from the set of questions, of which 48.2% of the total variance is explained. The first factor with a specific value of 10.8 equal to 22.5% of the total variance and finally the fifth factor with a special value of 2.4 about 5.1% justifies the variance of the total variables. Cronbach's alpha coefficient was the components of the tendency to modernism questionnaire between 0.69 and 90, indicating the appropriate validity of this tool. Conclusion: It can be concluded that the modernity tendency questionnaire in students has good validity and reliability for future research in Iran.